Defect-moderated oxidative etching of MoS2 - Zhang, Hongzhou (My University, 2019)
We report a simple technique for the selective etching of bilayer and monolayer MoS 2. In this work, chosen regions of MoS 2 were activated for oxygen adsorption and reaction by the application of low doses of He + at 30 keV in a gas ion microscope. Raman spectroscopy, optical microscopy, and scanning electron microscopy were used to characterize both the etched features and the remaining material. It has been found that by using a pretreatment to introduce defects, MoS 2 can be etched very efficiently and with high region specificity by heating in air.
PUBLISHED
cited By 1
Keywords: monolayer MoS 2; oxygen adsorption; scanning electron microscopy; Optical microscopy; Oxidation; 2D materials; Crystallographic defects; Scanning electron microscopy; Focused ion beam; Raman spectroscopy; Chemical vapor deposition; Nanoscience & Materials